Embodied reflexivity: discerning ethical practice through the Six-Part Story Method. Issue 2 (4th March 2019) - Vettraino, Elinor; Linds, Warren; Downie, Helen
ABSTRACT: Early reflective practice drew on the work of John Dewey and the concept of learning-by-doing involving individual reflection on, and in, action. More recently the practice of reflection has also been taken into a more socially constructed, and emergent, sense of knowing where the individual 'reflexes' in, and through, experiences as felt ways of knowing. This concept forms the basis of this article. We will explore a process of learning called the Six-Part Story Method (6PSM). Originally created in the field of dramatherapy as a diagnostic tool to enable child victims of trauma to be supported, Elinor further developed it in 2017 to support education professionals and leaders to enhance their reflective practice and create new opportunities to develop greater self-awareness. Warren then utilized it in teaching a course on ethical practice in a graduate programme; the course's epistemological underpinning is the concept of 'ethical know-how'. We then include the work of Helen, a student in the programme, as she explores the story she developed through the 6PSM and then analyzes the effect of it on herself one year later.